Ökonomische Bildung als gesellschaftliche Herausforderung Wege zu einer reflexiven Wirtschaftsdidaktik - Goldschmidt, Nils; Lenger, Alexander; Keipke, Yvette (Mohr Siebeck, 2020)
Only a (socio-) economic education geared to a developing a sense and understanding of how financial factors play out in society will ultimately give students the knowledge they require to successfully understand and master social and economic issues in a sustainable way.
PublicationDate: 20200805
Keywords: Kopftuch -- interdisziplinär -- Significance -- Tax Incentives For R+d -- Ökonomische Bildung -- Sozio-Ökonomische Bildung -- Wirtschaftliches Verstehen -- Wirtschaftsdidaktik -- Sozial-/Kulturwissenschaften -- Wirtschaftsordnung, Wirtschaftspolitik